How Might a Davidsonian Rescue the Normativity of Meaning? - Hossein Zadeh, Morteza Sedaghat Ahangari (Filozofia Nauki, 2013)
For meaning normativism to hold, meaning must have a constitutive part which is obligation-producing. I claim in this paper that linguistic communication is such a constitutive part. I try to show this by means of appeal to Davidson’s triangulation thesis. If I am successful, it may fairly be said that “a Davidsonian can rescue the normativity of meaning”.